Prevalence of type 2 inflammation in patients with chronic rhinosinusitis with nasal polyps in Saudi Arabia - Aldajani, Ahmad; Alroqi, Ahmad; Alramyan, Rana; Alhejin, Nujud; Alswayyed, Mohammed; Alrajban, Waleed A.; Alromaih, Saud; Aloulah, Mohammad O.; Alrasheed, Abdulaziz S.; Aldousary, Surayie; Alsaleh, Saad (Frontiers in Surgery, 2024)
Background Chronic Rhinosinusitis (CRS) is a common condition causing a significant worldwide burden, affecting 5%–12% of the general population. CRS is classified into type 2 and non-type 2 disease based on endotype dominance. Type 2 inflammation is distinguished by the presence of IL-4, IL-5, and IL-13 cytokines, along with eosinophil and mast cell activation and recruitment. Evidence of type 2 inflammation is ascertained by tissue eosinophil count >10/high-power field (HPF) or serum eosinophil >250 cells/mcL or total immunoglobulin E (IgE) > 100 IU/ml. Objectives To investigate the prevalence and characteristics of type 2 inflammation in patients who presented with nasal polyps and underwent Endoscopic Sinus Surgery (ESS) in Saudi Arabia. Design A retrospective cross-sectional Study. Methods This study was conducted among patients who presented with nasal polyps and underwent ESS at King Saud University Medical City (KSUMC) from 2015 to 2020. Patients with nasal/sinus diseases other than Chronic Rhinosinusitis with Nasal Polyps (CRSwNP) were excluded. Demographic data, olfaction status, and co-morbidities were collected, and radiological images were evaluated. Type 2-CRS was determined by meeting at least one of three predictor criteria (blood eosinophils ≥250 cells/mcL, tissue eosinophils ≥10/HPF, or total IgE levels ≥100 IU/ml). Blood parameters and histopathologic analysis were obtained for each patient. Results Of the 381 patients included in the study, the prevalence of type 2-CRS, based on the EPOS2020 criteria, was 99.7% in our population. Among these patients, 47.5% had hyposmia, 38.8% had anosmia, and 13.6% had normal olfaction. The most prevalent co-morbidity was allergic rhinitis, followed by bronchial asthma. Conclusion This study aimed to determine the prevalence of type 2 inflammation among patients Diagnosed with CRSwNP and underwent ESS in Saudi Arabia. The results showed a prevalence of 99.7%, indicating that almost all recorded patients with CRSwNP in our population had type 2 inflammation.